Using of Gel Extracted From Flax Seeds to Preserve The Quality Characteristics of Ground Beef Patties Stored in The Freezer: Penggunaan Gel yang Diekstrak dari Biji Rami untuk Mempertahankan Karakteristik Kualitas Roti Daging Sapi Giling yang Disimpan dalam Freezer - Shabeeb , Aliaa J.; Makki , Ghaidda Ali (Universitas Muhammadiyah Sidoarjo, 2024)
The current study aimed to use flaxseed gel at concentrations of,0.5% ,0.10 % and 0.15 % each in preserving beef meat by freezing at a temperature of -18°C. The chemical composition of the gel and chemical tests were conducted that included the peroxide number, the percentage of free fatty acids, and microbial tests. Which included the total a count of bacteria and Psychrophilic bacteria. The results showed a significant decrease in the values of peroxide and free fatty acids for meat samples treated with all concentrations of flaxseed gel. Compared to the control treatment, which exceeded the standard limits after 30 days of preservation While the processed meat tablets remained within the limits of the standard specification for freeze preservation during 120 days of preservation.. A significant decrease (p < 0.05) was also observed in the numbers of total bacteria and psychrophilic bacteria when meat was treated with flaxseed gel of different concentrations compared to the control treatment. The T2 treatment may be superior in reducing the numbers of bacteria compared to the rest of the treatments. The fourth and third treatments were superior in terms of general acceptance compared to the control treatment after 4 months of freezing. Highlights: Preservation: Flaxseed gel effectively reduces peroxide, fatty acids, and bacteria. Testing: Significant bacterial reduction observed with 0.15% concentration in frozen meat. Results: Treated meat remains acceptable for 120 days, surpassing control quality. Keywords: flax seeds, beef, anti microbial, beef freeze, , antioxidant.